On Octavius from Maloti-Drakensberg and Golden Gate National Parks, South Africa (Coleoptera: Staphylinidae: Euaesthetinae) - Janák, Jiří (Zootaxa, 2024)
Nineteen species of the genus Octavius Fauvel, 1873 from Maloti-Drakensberg and Golden Gate National Parks, South Africa were recognised. Thirteen species are described as new: Octavius aureaportalis Janák, sp. nov., O. clarkei Janák, sp. nov., O. flagellatus Janák, sp. nov., O. gracilis Janák, sp. nov., O. gxaligengwanus Janák, sp. nov., O. kambergensis Janák, sp. nov., O. lothenicus Janák, sp. nov., O. monachicucullus Janák, sp. nov., O. penicullatus Janák, sp. nov., O. regius Janák, sp. nov., O. squamatus Janák, sp. nov., O. subulatus Janák, sp. nov. and O. undulatus Janák, sp. nov., distribution records of additional six species of Octavius are presented and all species are illustrated.